La "mala leche": la Alianza para el Progreso y los rumores antiimperialistas en América Latina durante la década de 1960. - Flórez Malagón, Alberto G.; Agostoni, Claudia (Canadian Journal of Latin American & Caribbean Studies (Taylor & Francis Ltd), 2025)
This article seeks to study the impact of the food policy of the Alliance for Progress (1961–1970) from a broad geographic framework in the Latin American region. The text explores the role of rumors as political weapons in Latin America during the 1960s, focuses on the little-discussed case of the distribution of milk powder donated by the United States as part of that development program, and addresses how its consumption generated discursive resistance, mainly by anti-imperialist groups in the region, which linked the distribution of milk to a supposed case of forced sterilization. Why was it possible to present credible arguments in favor of this idea? The explanation seems to be based on the context of the Cold War, on the closeness of the Cuban experience and the counter-revolutionary intervention of the United States in the region, as well as on the debates about birth control fueled by left-wing ideologies such as the theory of liberation. Conspiracy theories about the regulation of Latin American population growth as a mechanism to control communism arose from there, which connected the US milk donations with a supposed biocontrol strategy exercised through a sterilization program in the region.